THE CHALLENGES OF USING TIK-TOK MEDIA ON SPEAKING CLASS - Suhartatik; Ovani Agting; Indrawati Pusparini (UIBU, 2022)
Tik-Tok application as teaching media is fit in with the students’ need and interests. The goal is to develop Tik-Tok application as media for teaching Speaking at the level of senior high school. Research and Development focus on the steps how to develop Tik-Tok media in the teaching of Speaking. The finding show that Tik-Tok media is needed in learning speaking with the score of 85%. The result of compatibility is also absolutely agreed that Tik-Tok media is compatible with the students’ characteristic (85%). The expertise judgment of Material and Media validate Tik-Tok media with the criteria of “very good” in the aspects of content and video application. It means that the development of Tik-Tok application is feasible to be used as media on Speaking class.